Application of antibody-conjugated small intestine submucosa to capture urine-derived stem cells for bladder repair in a rabbit model - Yu-Ting Song; Yan-Qing Li; Mao-Xuan Tian; Jun-Gen Hu; Xiu-Ru Zhang; Peng-Cheng Liu; Xiu-Zhen Zhang; Qing-Yi Zhang; Li Zhou; Long-Mei Zhao; Jesse Li-Ling; Hui-Qi Xie (Bioactive Materials, 2022)
The need for bladder reconstruction and side effects of cystoplasty have spawned the demand for the development of alternative material substitutes. Biomaterials such as submucosa of small intestine (SIS) have been widely used as patches for bladder repair, but the outcomes are not fully satisfactory. To capture stem cells in situ has been considered as a promising strategy to speed up the process of re-cellularization and functionalization. In this study, we have developed an anti-CD29 antibody-conjugated SIS scaffold (AC-SIS) which is capable of specifically capturing urine-derived stem cells (USCs) in situ for tissue repair and regeneration. The scaffold has exhibited effective capture capacity and sound biocompatibility. In vivo experiment proved that the AC-SIS scaffold could promote rapid endothelium healing and smooth muscle regeneration. The endogenous stem cell capturing scaffolds has thereby provided a new revenue for developing effective and safer bladder patches.